2018
DOI: 10.18778/0138-0680.47.2.02
|View full text |Cite
|
Sign up to set email alerts
|

Free Modal Pseudocomplemented De Morgan Algebras

Abstract: Modal pseudocomplemented De Morgan algebras (or mpM-algebras) were investigated in A. V. Figallo, N. Oliva, A. Ziliani, Modal pseudocomplemented De Morgan algebras, Acta Univ. Palacki. Olomuc., Fac. rer. nat., Mathematica 53, 1 (2014), pp. 65–79, and they constitute a proper subvariety of the variety of pseudocomplemented De Morgan algebras satisfying xΛ(∼x)* = (∼(xΛ(∼x)*))* studied by H. Sankappanavar in 1987. In this paper the study of these algebras is continued. More precisely, new characterization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…In this subsection, we will show that Theorem 5.1 has particular cases that was previously obtained in the literature in [19,15].…”
Section: Particular Casesmentioning
confidence: 53%
See 3 more Smart Citations
“…In this subsection, we will show that Theorem 5.1 has particular cases that was previously obtained in the literature in [19,15].…”
Section: Particular Casesmentioning
confidence: 53%
“…In what follows, we will study the prime spectrum of a given C k -algebra A with an algebraic technique. First, let us observe the study could be done using topological representation through the techniques given in [16,18]. Proposition 2.5 Let (A, t) be a C k -algebra and U ⊆ A an ultrafilter.…”
Section: Proof It Follows From the Very Definitions ✷mentioning
confidence: 99%
See 2 more Smart Citations
“…In [13], it was showed that every mpM −algebra is a TMA-algebra by defining ∇x = ∼ (∼ x ∧ x * ) and △x =∼ ∇ ∼ x, but the varieties are not equivalent as it was shown in [14,Section 5]. In [14] (see also [15]), the authors proved that the subdirectly irreducible mpM −algebras are three as displayed in the following Remark.…”
Section: Preliminariesmentioning
confidence: 98%